Problems and Enhancements of the Embedding of OCL into QVT ImperativeOCL - Büttner, Fabian; Kuhlmann, Mirco (Electronic Communications of the EASST, 2008)
MOF QVT introduces ImperativeOCL as an imperative language foroperational descriptions of model transformations (QVT operationalmappings). ImperativeOCL extends conventional OCL by expressions withside-effects. A couple of semantical problems arise from the way OCLis embedded into ImperativeOCL -- imperative expressions are modelledas a subtype of OCL expressions. This paper points out thesesemantical problems and proposes a change to the operational mappingslanguage of QVT that resolves these problems, following an approachthat reuses OCL by composition rather than by inheritance in theabstract syntax of ImperativeOCL. The proposed change reduces thecomplexity of the imperative language, removes undefinedness, andleaves OCL conformant to its original definition.